Cloning of Escherichia coli DNA that controls cell division and capsular polysaccharide synthesis - Berg, Patricia E. (1976)
A 2 × 10(6) dalton DNA fragment that controls cell division, capsular polysaccharide synthesis, and enzymes of capsular polysaccharide synthesis has been cloned.